2020
DOI: 10.1111/mcn.13065
|View full text |Cite
|
Sign up to set email alerts
|

High dietary micronutrient inadequacy in peri‐urban school children from a district in South India: Potential for staple food fortification and nutrient supplementation

Abstract: Multiple micronutrient deficiencies (MNDs) co‐exist, often because of poor intakes and adversely impact health. Habitual diets were assessed in 300 school children (6–17 years old) recruited from two government schools by simple random sampling. Probability of adequacy (PA) for 11 micronutrients and mean probability of adequacy (MPA) was calculated. Haemoglobin, plasma ferritin, folic acid, vitamin B 12 and C‐reactive protein were estimated. Descriptive statistics and regression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…This is in line with a study conducted in South India, that reported an inadequate intake of iron, vitamin B12, and folate in diet of peri-urban school children. ( 29 ) Another study from Manipur, an eastern state of India, reported children and adolescents have low dietary inadequacy of calcium and vitamin A. ( 30 ) The National Nutrition Monitoring Bureau (2011–12) reported that adequacy of calcium, iron, zinc, folate, vitamin A, and vitamin B12 intake was very poor in adolescent girls from ten states of India.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with a study conducted in South India, that reported an inadequate intake of iron, vitamin B12, and folate in diet of peri-urban school children. ( 29 ) Another study from Manipur, an eastern state of India, reported children and adolescents have low dietary inadequacy of calcium and vitamin A. ( 30 ) The National Nutrition Monitoring Bureau (2011–12) reported that adequacy of calcium, iron, zinc, folate, vitamin A, and vitamin B12 intake was very poor in adolescent girls from ten states of India.…”
Section: Discussionmentioning
confidence: 99%
“…6 Based on the health survey responses of 220 HCPs in urban India (Mar-Apr 2021), nearly 85% of Indian doctors (GPs, ENTs, Internal Medicine experts), and 93% of Indian nutritionists also believe that only 70% (or even lower) of our micronutrient requirements are fulfilled by our daily Indian diet in urban adults aged 25-45 years. 16 Majority of the HCPs agreed that among micronutrients, consumption of calcium, iron, folic acid, zinc, vitamin D3, and B12 are below RDA guidelines in the Indian population. Among MiNDs, iron deficiency anemia, vitamin A deficiency, and riboflavin deficiency are highly prevalent in the Indian population.…”
Section: Inadequacy Of Daily Diet To Fulfill Rda Of Micronutrientsmentioning
confidence: 99%
“…Based on the health survey responses of 220 HCPs in urban India (Mar-Apr 2021), 74% of Indian doctors/nutritionists are positively inclined to prescribe multivitamin/mineral supplements to fulfill micronutrient deficiencies (as per RDA) in daily Indian diet (Figure 3). 16…”
Section: Impact Of Multivitamin/mineral Supplementation On Immunity/e...mentioning
confidence: 99%
“…9 Alleviation of micronutrient deficiencies is imperative and is globally addressed through intervention strategies that include supplementation, fortification and food diversification. 10 Major health concerns connected to dietary inadequacy include lack of critical nutrients, protein-energy malnutrition and micronutrient inadequacies. 11 …”
Section: Introductionmentioning
confidence: 99%